IMPLEMENTASI METODE PENANAMAN KEDISIPLINAN OLEH GURU DI TK ABA PRINGGOKUSUMAN - Wati, Dewi Eko; Wandari, Sri; Puspitasari, Intan; Rohmadheny, Prima Suci (Buletin Literasi Budaya Sekolah, 2025)
Discipline instillation is a process of shaping attitudes and behaviors so that children can adhere to established rules, conducted routinely by educators at school. Based on observations at TK ABA Pringgokusuman, in instilling discipline in students, teachers use habituation and role-modeling methods. The habituation method is carried out by familiarizing children with disciplined activities on a regular basis, while the role-modeling method involves teachers directly demonstrating disciplined actions so that children can observe and imitate them. However, the researcher found some challenges related to discipline instillation in children, such as children arriving late, not tidying up toys after use, and not wearing school uniforms. This study aims to understand how the discipline instillation methods are implemented by teachers at TK ABA Pringgokusuman Yogyakarta. This research is qualitative with a case study approach, involving two teachers from class B and the principal as informants. Data collection methods include interviews, observations, and documentation, with data validity ensured through triangulation techniques. The researcher used Naughton and Hughes' theory for data analysis, which involves data collection, data coding, and data analysis. Regarding the implementation of discipline instillation methods by teachers at TK ABA Pringgokusuman, the results show that the application of daily routines, spontaneous activities, and the active role of teachers as role models positively influences children's discipline. These methods are effective in shaping disciplined attitudes through repeated activities and positive reinforcement, such as praise and rewards given by teachers at school. However, challenges include inconsistencies between discipline at home and school, lack of structured planning, and limited number of teachers and inadequate school facilities. To address these challenges, teachers strive for better collaboration with parents, improved planning, and enhanced school facilities to support the effectiveness of discipline instillation in children.